posted by Angelina on .
I don't understand how to solve this problem:
In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be
x + 3 = 48 => x = 45or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.
Eric is applying the zero principle to a non zero quantity.
Zero Principle: if AB=0, then A,or B, or both is zero.
Silly nonsense : if AB=C, then A, or B, equals C